Design of an Organic Template for Synthesizing ITR Zeolites under Ge-Free Conditions - Ma, Ye; Hu, Junyi; Fan, Kai; Chen, Wei; Han, Shichao; Wu, Qinming; Ma, Yanhang; Zheng, Anmin; Kunkes, Eduard; De Baerdemaeker, Trees; Parvulescu, Andrei-Nicolae; Bottke, Nils; et al. (Journal of the American Chemical Society, 2023)
Germanosilicate zeolites with various structures have been extensively synthesized, but the syntheses of corresponding zeolite structures in the absence of germanium species remain a challenge. One such example is an ITR zeolite structure, which is a twin of the ITH zeolite structure. Through the modification of a classic organic template for synthesizing ITH zeolites and thus designing a new organic template with high compatibility to ITR zeolite assisted by theoretical simulation, we, for the first time, show the Ge-free synthesis of an ITR structure including pure silica, aluminosilicate, and borosilicate ITR zeolites. These materials have high crystallinity, corresponding to an ITR content of more than 95%. In the methanol-to-propylene (MTP) reaction, the obtained aluminosilicate ITR zeolite exhibits excellent propylene selectivity and a long lifetime compared with conventional aluminosilicate ZSM-5 zeolite. The strategy for the design of organic templates might offer a new opportunity for rational syntheses of novel zeolites and, thus, the development of highly efficient zeolite catalysts in the future.